Genetics - Sambamurty, A. V. S. S. (Alpha Science International, 2005)
The second edition has been divided into five parts viz., Mendelian Genetics, Molecular Genetics, Cytogenetics, Plant Breeding and Genomics spanning about 900 pages with 250 diagrams and 150 worked problems. The Genomics part, added to this new edition, deals with experimentation in gene cloning, recombinant DNA technology and Human Genome project. It also includes an exhaustive glossary of Genetics, Plant Breeding and Molecular Genetics; questions, techniques in Cytogenetics like staining, fixation, preparation of permanent slides and a detailed historical development of Genetics from Mendel to recent times. New to the Second Edition: · More Human Genetic diseases discussed · Detailed Discussion on Drosophila and Caenorhabditis elegans · Applied aspects of Biotechnology in Plants · Gene cloning and recombinant DNA technology for crop improvement programmes